“Segunda Chamada”: the unsustainability of public education in serial fiction - Coca, Adriana Pierre (Comunicação & Educação, 2023)
This study focuses on how serialized fictional stories shape meanings when approaching the Sustainable Development Goals formally articulated in the United Nation’s 2030 Agenda. Brazilian series Segunda Chamada (Second Call), whose plot revolves around the challenges faced by a group of public school teachers on the outskirts of São Paulo city dedicated to adult education, was chosen to investigate, using culture semiotics and Lotman’s3 concepts of border and translation how serialized fiction constitute meaning translation regarding EJA. Segunda Chamada shows similarities to open TV serial narratives and discontinuities that update it to a digital context, even when under a modeling media culture system.